Epibrassinolide-Induced Autophagy Occurs in an Atg5-Independent Manner Due to Endoplasmic Stress Induction in MEF Cells - Adacan, Kaan; YERLİKAYA, PINAR OBAKAN; Çoker-Gürkan, Ajda; Kaya, Resul İsmail; Palavan-Ünsal, Narcin; ARISAN, ELİF DAMLA (Springer, 2020)
Epibrassinolide (EBR), a polyhydroxysteroid belongs to plant growth regulator family, brassinosteroids and has been shown to have a similar chemical structure to mammalian steroid hormones. Our findings indicated that EBR could trigger apoptosis in cancer cells via induction of endoplasmic reticulum (ER) stress, caused by protein folding disturbance in the ER. Normal cells exhibited a remarkable resistance to EBR treatment and avoid from apoptotic cell death. The unfolded protein response clears un/misfolded proteins and restore ER functions. When stress is chronic, cells tend to die due to improper cellular functions. To understand the effect of EBR in non-malign cells, mouse embryonic fibroblast (MEF) cells were investigated in detail for ER stress biomarkers, autophagy, and polyamine metabolism in this study. Evolutionary conserved autophagy mechanism is a crucial cellular process to clean damaged organelles and protein aggregates through lysosome under the control of autophagy-related genes (ATGs). Cells tend to activate autophagy to promote cell survival under stress conditions. Polyamines are polycationic molecules playing a role in the homeostasis of important cellular events such as cell survival, growth, and, proliferation. The administration of PAs has been markedly extended the lifespan of various organisms via inducing autophagy and inhibiting oxidative stress. Our data indicated that ER stress is induced following EBR treatment in MEF cells as well as MEF Atg5(-/-) cells. In addition, autophagy is activated following EBR treatment by targeting PI3K/Akt/mTOR in wildtype (wt) cells. However, EBR-induced autophagy targets ULK1 in MEF cells lacking Atg5 expression. Besides, EBR treatment depleted the PA pool in MEF cells through the alterations of metabolic enzymes. The administration of Spd with EBR further increased autophagic vacuole formation. In conclusion, EBR is an anticancer drug candidate with selective cytotoxicity for cancer cells, in addition the induction of autophagy and PA metabolism are critical for responses of normal cells against EBR.
Keywords: Epibrassinolide; ER Stress; Apoptosis; Autophagy; Polyamines